Hoxb1 Regulates Distinct Signaling Pathways in Neuromesodermal and Hindbrain Progenitors to Promote Cell Survival and Specification. Issue 2 (24th January 2022) - Pazur, Kristijan; Giannios, Ioannis; Lesche, Mathias; Rodriguez-Aznar, Eva; Gavalas, Anthony
Abstract: Hox genes play key roles in the anterior-posterior (AP) specification of all 3 germ layers during different developmental stages. It is only partially understood how they function in widely different developmental contexts, particularly with regards to extracellular signaling, and to what extent their function can be harnessed to guide cell specification in vitro. Here, we addressed the role of Hoxb1 in 2 distinct developmental contexts; in mouse embryonic stem cells (mES)-derived neuromesodermal progenitors (NMPs) and hindbrain neural progenitors. We found that Hoxb1 promotes NMP survival through the upregulation of Fgf8, Fgf17, and other components of Fgf signaling as well as the repression of components of the apoptotic pathway. Additionally, it upregulates other anterior Hox genes suggesting that it plays an active role in the early steps of AP specification. In neural progenitors, Hoxb1 synergizes with shh to repress anterior and dorsal neural markers, promote the expression of ventral neural markers and direct the specification of facial branchiomotorneuron (FBM)-like progenitors. Hoxb1 and shh synergize in regulating the expression of diverse signals and signaling molecules, including the Ret tyrosine kinase receptor. Finally, Hoxb1 synergizes with exogenous Glial cell line-derived neurotrophic factor (GDNF) to strengthen Ret expression and further promote the generation of FBM-like progenitors. Facial branchiomotorneuron-like progenitors survived for at least 6 months and differentiated into postmitotic neurons after orthotopic transplantation near the facial nucleus of adult mice. These results suggested that the patterning activity of Hox genes in combination with downstream signaling molecules can be harnessed for the generation of defined neural populations and transplantations with implications for neurodegenerative diseases. Graphical Abstract: